Motorola : the mobile phone business in China - Ang, Shan Shan (2008)
This project serves to provide a greater insight into Motorola's mobile phone business in China. The conditions in China were analysed and recommendations were made based on the marketing mix as to how Motorola can maintain its position as the leading mobile phone company in China.